2005
DOI: 10.1016/j.jpainsymman.2005.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Video-Thoracoscopic Surgical Pleurodesis in the Management of Malignant Pleural Effusion: The Importance of an Early Intervention

Abstract: Thoracentesis plays an important role in cancer patients with symptomatic effusions, although its effect is short-lived and symptoms recur in almost all patients. Early video-thoracoscopic surgical pleurodesis may provide added benefit to a group of patients with advanced cancer presenting with symptomatic malignant pleural effusion. Seventy-six patients with advanced cancer and pleural effusion due to pulmonary-pleural metastases were recruited. In 51 cases (67.1%), at least one thoracentesis was performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Talc has been reported as safe and efficacious for pleurodesis [15][16][17][18][19][20][21][22][23]. A Cochrane review reported that pleurodesis with talc provided the highest relative chance of MPE nonrecurrence when compared with bleomycin, tetracycline, mustine or chest-tube drainage alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…Talc has been reported as safe and efficacious for pleurodesis [15][16][17][18][19][20][21][22][23]. A Cochrane review reported that pleurodesis with talc provided the highest relative chance of MPE nonrecurrence when compared with bleomycin, tetracycline, mustine or chest-tube drainage alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…In these late treated cases, partial decortication had no effect on the re-expansion of the trapped lung. In their study, MARRAZZO et al (13) showed that early thoracocentesis plays an important role in cancer patients with symptomatic effusions. In their study, pleurodesis with talc poudrage was completely successful in all patients with a morbidity rate of 2.6%.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, postoperative pleural drainage was used until fluid output was less than 100 ml/24 h. For some authors (13,21), the chest tube could be removed within 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Another argument that strengthens the use of thoracoscopy in a PE clinically classifi ed as malignant or nonaffi liated is that approximately 60% of these patients need a pleurodesis during their evolution [15] and it should be done as soon as possible because a "trapped lung" invalidates the process [16]. Thoracoscopy not only provides a reliable diagnosis [17] but allows a therapeutic intervention to be performed that will have an effect only in early stages of the condition [18].…”
Section: Discussionmentioning
confidence: 99%